The Status of Ulayat Land of the Rempang Community in the Perspective of Deliberative Democracy - Belinda, Tasya Defana; Pamungkas, Susandi Decapriu Putra; Ramadhani, Pyaredika Majidah Izzati (Bagian Dasar-Dasar Ilmu Hukum & Hukum dan Masyarakat Fakultas Hukum Universitas Diponegoro, 2024)
The Rempang land tenure polemic has become an issue of injustice for indigenous communities regarding land management by the government. Article 19 of the UUPA is in line with the Rempang community's land ownership in order to ensure legal certainty by the government, so land registration is carried out with the agency that makes land deeds. However, the obstacle is that the Rempang community is not a traditional community but has rights to their ulayat land, which cannot easily mean that their ulayat land has a certificate. This research uses a normative juridical method with a conceptual approach by collecting data through literature studies to analyze topics with legal issues based on statutory regulations. The results of the research are expected to show government support through a historical approach to ulayat land and the application of deliberative democracy theory in order to realize the welfare of indigenous peoples which is the main goal as is the implementation of democratic principles.